Modeling of Specific Absorption Rate Distribution in Human Head Due to Far Field Electromagnetic Wave Radiation of 900 Mhz And 1800 Mhz Using the Method of Moment - Abdul Aziz, Nor Azah (2005)
In this study, a method of moment has been used to determine the induced electric field and specific absorption rate (SAR) distribution inside the human head due to far field electromagnetic wave radiation. Homogeneous and three layered spherical models were used to simulate a head of a two year old child at 900 MHz and 1800 MHz. In the models, the antenna was placed at 30 cm away fiom the head. The head was represented by 680 cells, suitable when using PC with Pentium IV processor and 512 MB DDR RAM memory. The method of moments (MOM) was employed to calculate the induced electric field which in turn can obtain the absorbed power, P,,; localized SAR, SAR; and averaged SAR, SAR, . The results of the calculated SAR were presented for the far field case. For both homogeneous and three layered models, the value of SAR were found higher at fkquency of 1800 MHz than 900 MHz. At both fiequencies, the three layered models have shown lower values of SAR. The results have shown the maximum absorbed power, localized SAR and averaged SAR are found in a homogeneous model at 1800 MHz, followed by three layered model at 1800 MHz, homogeneous model at 900 MHz and three layered model at 900 MHz. The averaged SAR for all models were in range 0.003 Wkg to 0.005 Wkg, which were still far behind the safety limit 0.08 Wkg averaged over 1 g of tissue. It was found that the behaviour of the localized SAR distribution were not uniform inside the head. It might be due to multiple reflection and absorption in the head. Besides, the incident electric field calculated in many angles might also contribute to the non-uniformity.